The Body as Evidence: Helping Clients Identify Decision-making Roadblocks - Synard, Jacqueline (Canadian Journal of Counselling and Psychotherapy, 2009)
Grad school or Europe for a year? A highly motivated, fourth-year liberal arts student makes her decision but still has doubts. What roles do emotion and a client’s personal history play in career counselling? The case study utilizes experiential process to uncover decision-making roadblocks.